2010
DOI: 10.1038/jhh.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of olmesartan medoxomil plus amlodipine in age, gender and hypertension severity defined subgroups of hypertensive patients

Abstract: Effective antihypertensive therapy is crucial for preventing cardiovascular events; however, blood pressure (BP) control rates remain poor. The objective of this analysis was to determine the efficacy of olmesartan/ amlodipine in age, severity and gender-based subgroups of patients with moderate-to-severe hypertension uncontrolled by amlodipine monotherapy. Patients with uncontrolled BP after 8 weeks' amlodipine 5 mg monotherapy (n ¼ 755) were randomized to continue amlodipine 5 mg or receive olmesartan (10-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This effect is almost certainly related to the higher baseline BP levels in the severe hypertension group, and has been observed in previous studies. 19,20 The impact of treatment on hypertension severity was also examined in a post-hoc analysis based on the ESH's classification system for BP/hypertension. This analysis revealed that, at baseline, the majority of patients had met the criteria for grade 2 or 3 hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is almost certainly related to the higher baseline BP levels in the severe hypertension group, and has been observed in previous studies. 19,20 The impact of treatment on hypertension severity was also examined in a post-hoc analysis based on the ESH's classification system for BP/hypertension. This analysis revealed that, at baseline, the majority of patients had met the criteria for grade 2 or 3 hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…According to a report by Schmieder and colleagues on the effects of CCB (amlodipine) monotherapy and CCB/ARB (olmesartan) combination therapy between the sexes, results demonstrated that a greater BP‐lowering effect on both SBP and DBP was observed in women compared with men. It has also been reported that this sex difference decreased as the dose of the ARB increased.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hypotension was similar across age groups (<65 years of age: 0.4 %; ≥65 years of age: 0.7 %); however, more participants ≥75 years of age (4.2 %) discontinued their study medication due to an adverse event compared with participants <65 years of age (2.2 %) and ≥65 years of age (2.9 %). OM either as monotherapy or in combination with HCTZ and/or AML is an effective and safe treatment for hypertension in a broad range of patients, including the elderly [3236]. In one study, 52–67 % of study participants ≥65 years of age receiving OM/HCTZ combination therapy achieved the SeBP goal of <140/90 mmHg, while in another study, 61 % of participants ≥65 years of age receiving OM/AML combination therapy, with or without HCTZ, achieved the SeBP goal of <140/90 mmHg (<130/80 mmHg in participants with diabetes) [32, 34].…”
Section: Discussionmentioning
confidence: 99%